The Influence of Education and Training on Professional Economics Education Teachers - Amiruddin Amiruddin; Zakaria Zakaria; Venny Arvianita (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2018)
The purpose of this research aimed to know the number of training which is followed by teachers during their working period as the teacher of economics. Furthermore, this study addressed to know the professional level of teacher, and to understand the influence of education and training to the professional teacher of economic education, research towards teachers of state high school in Banda Aceh. The approach used in this research is quantitative approach with descriptive research type while the sample was taken by using random sampling technique is only 28 economic teachers from 10 high schools in Banda Aceh. Data analysis technique is accomplished by using simple correlation analysis formula. There may be positive and significant relationship between education and training with professional economic education teachers in 10 state senior high schools in Banda Aceh,